Chimie organique notions fondamentales - Huot, Richard (Les éditions carcajou, 1994)
This book was digitized and reprinted from the collections of the University of California Libraries. Together, the more than one hundred UC Libraries comprise the largest university research library in the world, with over thirty-five million volumes in their holdings. This book and hundreds of thousands of others can be found online in the HathiTrust Digital Library. HP's patented BookPrep technology was used to clean artifacts resulting from use and digitization, improving your reading experience. Despite the cleaning process, occasional flaws may still be present that are part of the original book, reflecting the journey of these collections over a lifetime of use.